2017
DOI: 10.1002/jcp.26105
|View full text |Cite
|
Sign up to set email alerts
|

Cyanidin suppresses autophagic activity regulating chondrocyte hypertrophic differentiation

Abstract: Cartilage is a kind of special connective tissue which does not contain neither blood vessels nor lymphatics and nerves. Therefore, the damage in cartilage is difficult to be repaired spontaneously. Constructing tissue engineered cartilage provides a new technique for cartilage repairing. Mesenchymal stem cells (MSCs) possess a unique capability of self-renew and can differentiate into pre-chondrocytes which are frequently applied as seed cells in tissue engineering. However, in regenerated cartilage the chond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 50 publications
(51 reference statements)
1
9
0
Order By: Relevance
“…Importantly, we also provided evidence that a systemic Nrf2 deficiency results in Sox9 suppression in murine articular chondrocytes in vivo. At an older age, Nrf2-KO mice developed a mild osteoarthritic articular cartilage degeneration, which is in line with earlier reported proteoglycan loss upon postnatal Sox9 depletion [26]. Thus, we postulate that accumulative oxidative stress age-dependently contributes to cartilage degeneration in the knee and that Nrf2 helps protect its ECM integrity through maintaining Sox9-mediated postnatal tissue homeostasis.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Importantly, we also provided evidence that a systemic Nrf2 deficiency results in Sox9 suppression in murine articular chondrocytes in vivo. At an older age, Nrf2-KO mice developed a mild osteoarthritic articular cartilage degeneration, which is in line with earlier reported proteoglycan loss upon postnatal Sox9 depletion [26]. Thus, we postulate that accumulative oxidative stress age-dependently contributes to cartilage degeneration in the knee and that Nrf2 helps protect its ECM integrity through maintaining Sox9-mediated postnatal tissue homeostasis.…”
Section: Discussionsupporting
confidence: 91%
“…Further, a successful, direct pharmacological activation of Nrf2 target genes by methysticin has already been shown in vitro and in vivo in another context [ 24 , 25 ]. Interestingly, Cao et al [ 26 ] reported that cyanidin-induced Nrf2 overexpression reduced the relative mRNA expression of Sox9 and Col II in the murine embryonic mesenchymal progenitor cell line C3H10T1/2. At first glance, these data seemingly contradict our findings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One microgram of total RNA was reverse transcribed to single-stranded cDNA with a PrimeScript RT Reagent Kit (Takara, Nojihigashi, Japan). Table 1 shows the specific primers used in the quantitative real-time reverse transcription-polymerase chain reaction (qRT-PCR) (6). The cycling conditions were set as 95°C for 30 s and 40 cycles at 95°C for 5 s and 60°C for 30 s. The reference gene GAPDH was used for normalization to obtain the relative mRNA Western blot analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Modulation of autophagy is fundamental for cell differentiation in different cell types (i.e., myocytes, osteoblasts, neuronal cells, adipocytes, chondrocytes) [ 2 , 20 , 21 , 22 , 23 ]. The use of positive and negative modulators of autophagy have contributed to confirming this direct relation with chondrogenic differentiation [ 15 , 24 ]. It has been shown that autophagy activation contributes to suppressing the chondrogenesis of MSCs, while the reduction of the autophagic process contributes to the activation of MSCs chondrogenesis [ 25 ].…”
Section: Introductionmentioning
confidence: 99%